Innovations Enabling the Continued Extendibility of Cu and Post-Cu Damascene BEOL Technologies - Edelstein, D.; Jog, A.; Nguyen, S.; Huang, H.; Ghosh, S.; Choi, S.; Lanzillo, N.; Lofaro, M.; McDermott, S.; Metzler, D.; Mignot, Y.; Nogami, T.; et al. (Proceedings of the IEEE International Interconnect Technology Conference, 2025)
We review Cu dual damascene BEOL technology's key historic innovations, and continue forward through present leading-edge into the future. Several recent innovations are combined to extend Cu scaling, preserving industry-leading performance, reliability, and extendibility. These include a novel barrier-like low-k ILD, a novel damascene patterning solution, and a novel Cu metallization process. This combination enables further Cu barrier/liner and aspect-ratio scalings beyond others' predictions. Thus we reduce Cu nanowire RC significantly below the industry trend, starting at 2 nm node (24 nm and 21 nm pitches), while actually raising the highest TDDB and EM reliabilities. We propose a new path for damascene BEOL extendibility beyond Cu, without changing the BEOL integration and tooling infrastructure. For this, we demonstrate the first Rh damascene wiring and are researching post-metal anisotropic conductors, still in an damascene arechtecture and infrastructure. With these advents, we predict a large shift "to the left" (smaller dimensions) in BEOL R and RC crossover projections compared to HAR sub-etched Ru.